Highly glycosylated human alpha interferon: An insight into a new therapeutic candidate - Ceaglio, Natalia Analia (2010)
The type I human interferon alpha (hIFN-α) family consists of small proteins that exert a multiplicity of biological actions including antiviral, antiproliferative and immunomodulatory effects. However, though administration of recombinant hIFN-α2b is the current treatment for chronic hepatitis B and C and for some types of cancers, therapy outcomes have not been completely satisfactory. The short serum half-life and rapid clearance of the cytokine accounts for its low in vivo biological activity. Here we describe and characterize a long-acting rhIFN-α2b mutein, 4N-IFN, which has been created by introducing four N-glycosylation sites via site-directed mutagenesis. The hyperglycosylated protein was found to have a 25-fold longer plasma half-life than the non-glycosylated rhIFN-α2b, even greater than the commercial pegylated derivative Intron-A PEG. In addition, glycosylation increased the in vitro stability of the mutein against serum protease inactivation. Interestingly, despite its lower in vitro activity, 4N-IFN showed a markedly enhanced in vivo antitumor activity in human prostate carcinoma implanted in nude mice. MALDI-TOF MS and HPAEC-PAD carbohydrate analyses revealed the presence of high amounts of tetrasialylated (40%) and trisialylated (28%) N-glycan structures, which are consequently responsible for the improved characteristics of the cytokine, making 4N-IFN a new therapeutic candidate for viral and malignant diseases.